Multi-level evidence reveals PANK2 as a potential target of PFOA/PFOS-induced bone metabolism disruption: From network toxicology to in vitro validation - Yiming Shao; Wenhao Fan (Ecotoxicology and Environmental Safety, 2025)
Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) are two representative per- and polyfluoroalkyl substances (PFAS) that have attracted increasing attention due to their environmental persistence and potential health risks, while their bone toxicity remains unclear. In this study, we systematically investigated the toxicological mechanisms of PFOA and PFOS on bone metabolism by integrating network toxicology, molecular docking and molecular dynamics simulations, and in vitro cellular experiments. Pantothenate kinase 2 (PANK2) was identified as a key target through the intersection of multiple databases and cross-validation using three machine learning algorithms. Molecular docking and dynamics simulations demonstrated that PFOA and PFOS can stably bind to PANK2 protein. In vitro experiments further confirmed that both PFOA and PFOS significantly suppressed PANK2 expression in bone marrow mesenchymal stem cells (BMSCs), leading to a disruption in the balance between osteogenic and adipogenic differentiation. Additionally, gene set enrichment analysis (GSEA) suggested that PANK2 may participate in bone metabolic regulation via chemokine signaling pathway and the neuro-osteogenic axis. This study highlights for the first time the critical role of PANK2 in PFAS-induced osteoporosis and provides novel mechanistic insights and potential therapeutic targets for the prevention and treatment of environmentally induced bone metabolic disorders.